Organisation de la coopération économique - Un pont stratégique entre le Moyen-Orient et l'Asie centrale (Note) - Hassan-Yari, Houchang (Études internationales, 1997)
The Economic Cooperation Organization has been created by Iran, Turkey and Pakistan to improve the trade and economic exchanges between the participating states. After the demise of the Soviet Empire, the Central Asian Republics, Azerbaijan and Afghanistan have joined the Organization. The internal problems of the ten States members OJECO have been aggravated by foreign intervention, especially the Russian hegemony over the region. This interference complicates the integration process and jeopardizes the effectiveness of the Organization.